Clinical and diagnostic aspects of carotid artery lesions in patients with type 2 diabetes mellitus: A scoping review - V. S. Arakelyan; A. K. Zhane; V. G. Papitashvili; M. I. Bykov; I. N. Shchanitsyn; V. V. Vulf (Kuban Scientific Medical Bulletin, 2026)
Background. As a key driver of atherosclerotic progression in the brachiocephalic arteries, type 2 diabetes mellitus substantially increases the risk of ischemic cerebrovascular events. Objective. To synthesize and analyze data on the morphological features, clinical course, and diagnosis of extracranial carotid artery atherosclerosis in patients with type 2 diabetes mellitus. Methods. A scoping review of the literature was conducted in accordance with the study objective. The literature search was conducted across the eLIBRARY.RU, PubMed, and CyberLeninka electronic databases, supplemented by manual searches using the Yandex search engine. Russian and foreign studies published between 2006 and 2026 were included. All stages of literature search, selection, and analysis were performed in accordance with the PRISMA-ScR guidelines. Results. A total of 32 studies were included in the review. This review synthesizes current data on the clinical and morphofunctional characteristics of extracranial carotid artery lesions in patients with type 2 diabetes mellitus. Particular attention is given to the pathogenetic mechanisms underlying the formation of unstable atherosclerotic plaques, the impact of hyperglycemia and insulin resistance on the vascular wall, and the clinical course of ischemic stroke and chronic cerebrovascular insufficiency in this patient population. Current diagnostic modalities — including duplex ultrasound, magnetic resonance imaging, and transcranial Doppler ultrasonography — as well as laboratory markers of vascular inflammation, were analyzed. Conclusion. The presence of carotid atherosclerosis in patients with type 2 diabetes mellitus leads to a more aggressive disease course, development of unstable atherosclerotic plaques, and an elevated risk of cerebrovascular complications. A comprehensive diagnostic approach enables a more accurate stroke risk assessment and guides the selection of optimal management strategies.